Case Report: Chemotherapy-free treatment with camrelizumab and anlotinib for elderly patients with KRAS and TP53 mutated advanced lung cancer - Qi, Wenbo; Xi, Dayong; Bai, Yuping; Liu, Le; Ma, Yanling; Yin, Zhenyu; Chen, Hao (Frontiers in Pharmacology, 2023)
Background: Lung cancer is a major public health issue and an enormous burden on society in China. Most lung cancers occur in elderly patients with non-small cell lung cancer (NSCLC), and many factors limit their treatment options. Chemotherapy-free therapy can avoid psychological fear, treatment pain, and adverse reactions caused by chemotherapy. Patients with NSCLC with TP53 gene mutations or KRAS gene mutations tend to be more sensitive to anlotinib or PD-1 drugs. However, KRAS is a proto-oncogene downstream of the epidermal growth factor receptor (EGFR) gene; therefore, if the KRAS gene has an activating mutation, EGFR-targeted drug resistance may occur. Further studies are needed to explore whether patients with dual KRAS and TP53 mutations can be treated with targeted immunotherapy without chemotherapy. Case presentation: A 74-year-old man was referred to the Lanzhou University Second Hospital due to chest tightness, shortness of breath, and weight loss for two months and was diagnosed with moderately to poorly differentiated adenocarcinoma. Laboratory examinations showed increased tumor marker levels, and gene sequencing indicated mutations in KRAS and TP53. Immunohistochemical analysis showed positive PD-L1 expression. Peripheral blood immune checkpoint test using flow cytometry indicated that the PD-1+CD8 levels were positive. After multi-disciplinary treatment, therapy with a combination of anlotinib and camrelizumab was initiated. Camrelizumab 200 mg was administered intravenously once every three weeks. Anlotinib 12 mg was administered orally daily before breakfast for two weeks with a week of rest in every cycle of 21 days. A reduction in tumor maker levels was observed up to the first cycle, which decreased within the normal limits up to the second cycle and continued until the eighteenth cycle. The patient's chest tightness, shortness of breath, weight loss, and other symptoms significantly improved following treatment. Computed tomography imaging showed that the neoplastic lesion was dramatically reduced. The patient is currently being followed-up for more than two years to evaluate the duration of the response. Conclusions: Chemotherapy-free immunotherapy combined with targeted therapy is an effective treatment for advanced NSCLC in elderly patients with KRAS and TP53 mutations. Such therapies should be supported with further clinical studies with larger sample sizes.